(untitled) (International Journal of Physiotherapy, 2014)
Background: Modified radical mastectomy is a frequent surgery employed as a therapeutic procedure in patients with breast carcinoma with involvement of axillary lymph nodes. Many patients suffer from severe shoulder complaints after axillary lymph node dissection even with postoperative rehabilitation. Pre-operative exercise and education are recommended to reduce the incidence of breast cancer related upper limb dysfunction; it will shorten the recovery time. The objectives of the study are to determine the influence of pre-operative physiotherapy on shoulder ROM using goniometer in subjects with modified radical mastectomy and to determine the influence of pre-operative physiotherapy on functional activities using shoulder pain and disability index (SPADI) in subjects with modified radical mastectomy. Methods: 30 Subjects of adult women included in the study who met the inclusion criteria, divided into 2 groups. Experimental Group received preoperative physical therapy education and exercises 1-2 weeks before surgery and routine physical therapy protocol after surgery. Control Group received standard education brochure preoperatively and routine physical therapy post operatively. Measurements included shoulder ROM and functional evaluation using goniometer and SPADI. Measurements were taken at baseline i.e., pre operatively, post operatively at 4th day after removal of drains, and 1month after surgery. Results: All measures were significantly reduced after surgery, but most recovered after 1month of surgery and attained functional level in experimental Group. Conclusion: This study provides experimental evidence that preoperative education and exercise influence the postoperative shoulder ROM and functional activities after modified radical mastectomy.